Internet connectivity disruption in Kazakhstan (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Kazakhstan. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: KZ-2026-0066. Severity: critical. Confidence: 70%